Moderate intensity cycling is better than running on recovery of eccentric exercise-induced muscle damage. (July 2021) - de Azevedo Franke, Rodrigo; Rodrigues, Rodrigo; Geremia, Jeam Marcel; Teixeira, Bruno Costa; Boeno, Francesco; Rabello, Rodrigo; Baroni, Bruno Manfredini; Lima, Cláudia Silveira
Abstract: Objective: To compare the effects of moderate intensity running and cycling on markers of exercise-induced muscle damage in men. Study design: Randomized controlled trial. Setting: Laboratory. Participants: Thirty volunteers were randomized in three groups [running (RG; n = 10), cycling (CG; n = 10) and control (CON; n = 10)] and were evaluated at baseline, post 24, 48 and 72 h of knee extensors' muscle damage protocol. CON performed passive recovery, while RG and CG performed active recovery immediately after the protocol, as well as 24 h and 48 h afterwards. Main outcomes: (i) maximal voluntary isometric contraction (MVIC); (ii) delayed-onset muscle soreness (DOMS); (iii) plasma creatine kinase (CK) and lactate dehydrogenase (LDH) levels. Results: No group-by-time interaction was found in any outcome evaluated (p > 0.05). All groups presented decreases in MVIC and increases in DOMS (p < 0.001), without differences in CK and LDH. Compared with CON, exercise groups presented likely beneficial effects for LDH, while only CG had a likely beneficial effect for DOMS. Lastly, CG presented likely/very likely beneficial effects for MVIC and DOMS compared to RG. Conclusion: Although the null hypothesis analysis did not find differences, the magnitude-based inference analysis suggested that moderate intensity cycling have likely beneficial effects on knee extensor muscle recovery after eccentric exercise protocol. Highlights: Active recovery is the most prescribed technique to recover after muscle damage. Running and cycling are widely used by athletes in regenerative training sessions. Cycling recovery is better than passive recovery in decreasing LDH and pain levels. Running recovery is better than passive recovery in decreasing LDH levels. Cycling is better than running recovery in the improvement of strength and pain.